2011
DOI: 10.1161/cir.0b013e318219661d
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Play: Innovations in Getting Active Summit 2011

Abstract: Background-To examine the influence active-play video gaming (also referred to as exergaming, exertainment, and active gaming) might have on improving health-related skills, enhancing self-esteem and self-efficacy, promoting social support, and ultimately motivating positive changes in health behaviors, the American Heart Association convened The Power of Play: Innovations in Getting Active Summit. The summit, as well as a follow-up science panel, was hosted by the American Heart Association and Nintendo of Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 33 publications
5
62
0
14
Order By: Relevance
“…The results about the level of physical activity involving exergames are aligned with the literature in which it has been observed that the classes with exergames provide to the schoolchildren the permanence of an expressive period of time in level of activities considered as moderated or vigorous (Lieberman, 2011;Pereira, Rodrigues, Campos, & Santo, 2013). The study of Shayne, Fogel, Miltenberger, and Koehler (2012), where the effects of exergames and the traditional physical education were compared among four active children indicated that the students were very involved in the practice of exergames and it was possible to involve the students in different ways of physical activities/exercises.…”
Section: Discussionsupporting
confidence: 82%
“…The results about the level of physical activity involving exergames are aligned with the literature in which it has been observed that the classes with exergames provide to the schoolchildren the permanence of an expressive period of time in level of activities considered as moderated or vigorous (Lieberman, 2011;Pereira, Rodrigues, Campos, & Santo, 2013). The study of Shayne, Fogel, Miltenberger, and Koehler (2012), where the effects of exergames and the traditional physical education were compared among four active children indicated that the students were very involved in the practice of exergames and it was possible to involve the students in different ways of physical activities/exercises.…”
Section: Discussionsupporting
confidence: 82%
“…Among others, Bogost 19 defines exergames as "games that combine play and exercise", and "that use physical input devices". Likewise, Lieberman et al 20 define activeplay video games, a term they suggest be used as a synonym for exergames, as games that "have an interface that requires physical exertion to play the game". Building on this understanding of exertion interfaces, Mueller et al 21 define exergames as games "in which the outcome is predominantly determined by physical effort".…”
Section: Definition and Theoretical Frameworkmentioning
confidence: 99%
“…Limited studies comparing active with passive video games indicate that activity-promoting video games lead to increased energy expenditure when compared with sedentary video games in healthy children (14). T erapeutic applications of existing video games were recently reviewed (19) and are also the subject of discussions at the annual Games for Health conference sponsored by the Robert Wood Johnson Foundation (http://www.gamesforhealth.org).…”
Section: Healthy Video Gamesmentioning
confidence: 99%